The role of digital technologies in increasing the competitiveness of branded products - N. V. Kokoreva; S. A. Silina (Вестник университета)
In the conditions of increasing market competition and standardization of product offerings, the problem of forming the companies’ competitiveness remains urgent. The purpose of the study is to develop practical recommendations for improving the competitiveness of branded products through the introduction of digital technologies. To achieve the goal, a behavioral and active approach to competition is applied. Competitiveness is considered as the result of actions that strengthen the company’s competitive position in the market. The possibility of using digital technologies in the process of creating additional consumer value as the basis for the competitiveness of the product offer is investigated. The results of the analysis of scientific publications and best practices in the field of development and implementation of digital technologies in the economic activities of market relations entities are presented. The novelty of the research lies in identifying the role of the use of digital technologies in increasing the competitiveness of branded products and determining the conditions for their successful implementation to achieve the objectives of forming the competitive advantages of the company. The results of the analysis allowed us to draw the following conclusions: companies, when forming competitive advantages with the help of digital tools, need to develop purposefully comprehensive digitalisation programs, and not be limited to the implementation of short-term projects for the introduction of a particular technology; identify and implement a strategy for creating value for consumers that would be inaccessible to competitors; coordinate the resources and efforts available to the organization in terms of the formation of digital competencies of employees.